Pengaruh Perceived Price Terhadap Willing To Buy Jasa Transportasi Indriver dengan Perceived Quality Sebagai Mediator - Muzhofar, Rifky Surya; Widodo, Arry (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Transportation is a fundamental necessity for individuals across all social strata. An efficient transportation system ensures that people can easily traverse geographical distances, connect various communities, and facilitate interactions. The proliferation of online transportation companies has led to increased competition in the industry. As a result, these companies are increasingly focused on creating attractive promotions to influence users' decisions when choosing which application to use. To stand out in this crowded market, companies often introduce various promotions and discounts to attract potential customers. InDrive, a ride-hailing platform, distinguishes itself in the competitive market by offering unique and innovative features: price negotiation. The benefits of this feature include serving price-conscious consumers and offering flexibility to find a ride with a tariff that matches their budget. This innovative approach can generate cost savings for users while providing additional income opportunities for drivers. The research population consists of Telkom University students from the 2021-2023 cohorts, with 100 respondents selected through online questionnaires distributed via social media. The sampling method used was simple random sampling, and the data was analyzed using SPSS. The research findings indicate that the perception of price and the perception of quality on the InDrive application have a significant relationship, quality perception affects the willingness to buy InDrive transportation, price perception affects the willingness to buy InDrive transportation, and quality perception serves as a mediator between price perception and the willingness to buy..